ANALISIS KELAINAN GENETIK - Miftahul Khairani; Ade Sekar Anggraini; Ayu Riski Aulia; Fany Erlangga Saragih; Faritz Khairuddin (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of the study was to analyze genetic disorders in humans based on 10 national and international based journals. This research method uses a literature review design. From the results obtained, the pure genetic disease found was Down syndrome, with a total of 13 cases in four years. Other diseases that can be influenced by genetic factors such as primary hypertension, asthma, and schizophrenia were also found in sig1nificant numbers.